2021
DOI: 10.1159/000518262
|View full text |Cite
|
Sign up to set email alerts
|

New Parameter of the Second Half of the P-Wave, P-Wave Duration, and Atrial Conduction Times Predict Atrial Fibrillation during Electrophysiological Studies

Abstract: Highlights of the Study• Atrial fibrillation that occurs during electrophysiological studies is an indicator of electrical vulnerability. • We report a new predictor of atrial fibrillation within the second half of the P-wave.• The new parameter, maximum Ppeak-Pend, is an independent predictor of atrial fibrillation in electrophysiological studies. • Atrial conduction times predict the occurrence of atrial fibrillation during electrophysiological studies better than P-wave parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Atrial size is an important factor for the perpetuation of AF since it facilitates the development of re-entry circuits by increasing the conduction time [ 35 , 50 , 57 ]. However, whilst a prolongation in P wave duration is commonly associated with AF [ 4 , 5 , 12 , 46 , 58 ], only a few studies have related the increase in P wave duration to atrial enlargement per se [ 59 , 60 ]. In athletes, lifetime training hours were associated with the prolongation in P wave duration and an increase in left atrial volume in one study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrial size is an important factor for the perpetuation of AF since it facilitates the development of re-entry circuits by increasing the conduction time [ 35 , 50 , 57 ]. However, whilst a prolongation in P wave duration is commonly associated with AF [ 4 , 5 , 12 , 46 , 58 ], only a few studies have related the increase in P wave duration to atrial enlargement per se [ 59 , 60 ]. In athletes, lifetime training hours were associated with the prolongation in P wave duration and an increase in left atrial volume in one study [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of P-wave morphology can reveal important information about atrial depolarization. Increase in P-wave duration may occur in pathological conditions such as nonhomogeneous and discontinuous atrial conduction leading to atrial enlargement and may be harbinger for atrial arrhythmias such as atrial fibrillation ( Carmona Puerta et al, 2021 ). In our study, we found that P-wave duration is not significantly different between AF players and other nondisabled groups.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the second P-wave part in clinical environment was recently appreciated in a study that investigated the correlation of P-wave parameters with inter- and intra-atrial conduction times measured via invasive analysis, finding a relatively high correlation between the second P-wave part and LA conduction times [ 52 ]. The study additionally used surface and invasive parameters to discern between AF occurrence and non-AF occurrence during electrophysiological studies of a randomly chosen set of patients.…”
Section: Discussionmentioning
confidence: 99%